Auditory stimulation and cardiac autonomic regulation - Vitor E. Valenti; Heraldo L. Guida; Ana C. F. Frizzo; Ana C. V. Cardoso; Luiz Carlos M. Vanderlei; Luiz Carlos de Abreu (Clinics, 2012)
Previous studies have already demonstrated that auditory stimulation with music influences the cardiovascular system. In this study, we described the relationship between musical auditory stimulation and heart rate variability. Searches were performed with the Medline, SciELO, Lilacs and Cochrane databases using the following keywords: "auditory stimulation", "autonomic nervous system", "music" and "heart rate variability". The selected studies indicated that there is a strong correlation between noise intensity and vagal-sympathetic balance. Additionally, it was reported that music therapy improved heart rate variability in anthracycline-treated breast cancer patients. It was hypothesized that dopamine release in the striatal system induced by pleasurable songs is involved in cardiac autonomic regulation. Musical auditory stimulation influences heart rate variability through a neural mechanism that is not well understood. Further studies are necessary to develop new therapies to treat cardiovascular disorders.